UV-spectrophotometric Method Development and Validation for Piperine Estimation in Black Pepper, Ayurvedic Formulation and Novel Nano Formulation: A Perfect Quality Assessment Tool - Patil, Akshay Kalgonda; Jalalpure, Sunil Satyappa; Chimagave, Supriya Suresh; Kurangi, Bhaskar Kallappa (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim: The current study aims to establish and validate a UV-spectrophotometric approach for estimating piperine in black pepper, commercial Ayurvedic preparation, and novel piperine-loaded nanoformulation. Materials and Methods: The UV-spectrophotometric technique was developed using methanol as a solvent. Piperine showed the absorbance at 342 nm. In accordance with ICH Q2 (R1) guidelines, the developed method was extensively validated in terms of selectivity, linear range, precision, accuracy, robustness, ruggedness, and reproducibility. The new method was also effectively used for precise estimation of piperine in black pepper, commercial Ayurvedic preparation and novel piperine loaded nanoformulation. The stability indicating study of the established UV-spectroscopic approach was carried as per as per ICH Q1A (R2) guidelines. Results: The optimal parameters for piperine analysis were established using methanol as solvent. With the line equation y = 0.067x + 0.005, the maximum absorption wavelength was found to be 342 nm. Between concentration ranges of 0.5–32μg/ mL, it showed a linear response. The linear regression coefficient was found to be 0.999. The method's linearity, accuracy, ruggedness, specificity, and sensitivity were all validated, and all validation results were confirmed to be in acceptable ranges. Piperine was found to be stable and less prone to degradation under acidic, basic, thermal and photolytic stress conditions whereas oxidation degradation showed extremely degradable characteristics. Conclusion: The established approach will serve as standard quality control tool for precise estimation of piperine in herbal formulations and can be used for quality analysis
Keywords: Piperine; Ayurvedic Preparation; UV-spectroscopic; Black pepper; Nanoformulation; ICH